A major increase of thromboembolic events in total hip and knee arthroplasty patients during the COVID-19 pandemic. Issue 1 (1st January 2022) - Villa, Jesus M.; Pannu, Tejbir S.; Piuzzi, Nicolas S.; Krebs, Viktor; Riesgo, Aldo M.; Higuera, Carlos A.
ABSTRACT: Objectives: The first known COVID-19 patient in the United States was reported on 1/20/2020. Since then, we noted increased thromboembolic events among our THA/TKA patients. Therefore, we sought to determine: (1) monthly incidences of pulmonary embolism (PE)/deep vein thrombosis (DVT) before and after January/2020 and (2) thromboembolic event rates for primary and revision patients. Methods: We retrospectively obtained from our electronic-medical-records the total monthly number of patients (December/2018-March/2021) who underwent primary or revision THA/TKA, and among them, those who had PE/DVT during each month. Monthly rates of thromboembolic events were calculated and figures were created showing rates throughout time. The cutoff month to define before and after COVID-19 was January/2020. Results: During the study period, 1.6% of patients (312/19068) had PE/DVT [PE (n = 102), DVT (n = 242), both (n = 32)]. Overall rate of PE/DVT before January/2020 was 1.2% (119/9545) and it was 2.0% (193/9523) after that month. Incidences of PE/DVT on April/June/July of 2020 were 3.4%, 3%, 3.4%, respectively. A major increase, when compared to 2019 (1.3%, 1%, 1%, respectively). An unusually high rate of PE was observed on April/2020 (3.4%), more than three times the one observed in any other month. After January/2020, there was an overall major increase of PE/DVT rates, but particularly among revision patients: 6% in five different months including 11.5% on November/2020. Conclusion: There was a major increase of thromboembolic events among THA/TKA patients during the COVID-19 pandemic, predominantly in revision patients. Patients need counseling about this increased risk. It remains uncertain whether more aggressive thromboprophylactic regimes should be followed.